1990
DOI: 10.1002/jrs.1250210210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of addition of potassium chloride to silver colloids

Abstract: The influence on silver colloids of the addition of KCI was directly investigated by means of transmission electron microscopy (TEM). It was found that the particle size increased and the surfaces of the crystal particles of the silver became covered with an overlayer. Additionally, the pattern of aggregation was found to be chain-like. These changes were very different from those caused by adding pyridine. The mechanism affecting the colloid and the intensity of the surfaceenhanced Raman scattering signals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…It is shown in the literature that the addition of chloride, most often in the form of KCl, to a colloidal suspension can induce supplementary enhancements when excited in the visible region. [33][34][35] The effect of the chloride ions most likely induces a reorientation of the adsorbate on the colloidal surface and results in the narrowing of some bands and a change in the relative intensity of certain vibrational modes. 34 Furthermore, it is shown that the addition of chloride leads to aggregation of the silver particles 33 as well as the formation of colloidal clusters, which significantly increases both the electromagnetic and chemical enhancement factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown in the literature that the addition of chloride, most often in the form of KCl, to a colloidal suspension can induce supplementary enhancements when excited in the visible region. [33][34][35] The effect of the chloride ions most likely induces a reorientation of the adsorbate on the colloidal surface and results in the narrowing of some bands and a change in the relative intensity of certain vibrational modes. 34 Furthermore, it is shown that the addition of chloride leads to aggregation of the silver particles 33 as well as the formation of colloidal clusters, which significantly increases both the electromagnetic and chemical enhancement factors.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35] The effect of the chloride ions most likely induces a reorientation of the adsorbate on the colloidal surface and results in the narrowing of some bands and a change in the relative intensity of certain vibrational modes. 34 Furthermore, it is shown that the addition of chloride leads to aggregation of the silver particles 33 as well as the formation of colloidal clusters, which significantly increases both the electromagnetic and chemical enhancement factors. 35 Daily trial runs were conducted to determine the specific amount of KCl required to a obtain the greatest SERS response.…”
Section: Methodsmentioning
confidence: 99%
“…Further addition of salt beyond the point of neutralizing the electrostatic charge proves detrimental to the fluorescence signal enhancement. Zhang et al [47] attribute this to a migration of loosely attached Ag atoms upon bonding with Cl − ions which later reattach to form a thin layer of non-crystalline Ag of high light absorptivity and low conductivity. In their work, electron micrographs show geometrical changes in the aggregated Ag nanoparticles which cause smoothing in the transitional areas between neighboring nanoparticle surfaces.…”
Section: Microfluidic-controlled Dropletsmentioning
confidence: 98%
“…Low concentrations of salt allow the particles to become neutrally charged, enabling the aggregation process to occur at a rapid rate. Higher concentrations of salt react with the Ag particles to create a loosely attached, nonconductive layer, reducing the development of SPs, and thus inhibit MEF [47] fluorescence enhancement when mixed with the Ag colloids. Further addition of salt beyond the point of neutralizing the electrostatic charge proves detrimental to the fluorescence signal enhancement.…”
Section: Microfluidic-controlled Dropletsmentioning
confidence: 99%
“…[21][22][23][24] However, the mechanism of the activation has not yet been fully explained. [25][26][27][28][29] One possible explanation is based on the formation of silver particle aggregates. 29 Recently, it has been shown that a very strong increase in the Raman signal is achieved in nanocrystal junction sites between two nanoparticles.…”
Section: Introductionmentioning
confidence: 99%